Self-Assembled Protein–Polymer Nanoparticles via Photoinitiated Polymerization-Induced Self-Assembly for Targeted and Enhanced Drug Delivery in Cancer Therapy - Gayathri R. Ediriweera; Yixin Chang; Wenting Yang; Andrew K. Whittaker; Changkui Fu (Molecules)
Protein–polymer bioconjugates offer numerous advantages in biomedical applications by integrating the benefits of functional proteins and tunable synthetic polymers. Developing drug-loaded protein–polymer nanoparticles, with a receptor-targeting protein forming the nanoparticle shell, would be ideal for the targeted delivery of drugs to cancer cells that overexpress specific receptors for more effective cancer therapy. In this study, we report the synthesis of reduction-responsive protein–polymer nanoparticles by a photoinitiated polymerization-induced self-assembly (photo-PISA) approach. Anti-cancer drugs can be efficiently encapsulated at high concentrations within the nanoparticles during the photo-PISA process. These protein–polymer nanoparticles present transferrin (Tf) on their surfaces, capable of targeting the overexpressed Tf receptors found on cancer cells. It was found that the nanoparticles demonstrate enhanced cellular uptake and delivery of the anti-cancer drug, curcumin, to cancer cells via Tf receptor-mediated endocytosis, compared to the control PEGylated nanoparticles that lack targeting capability. Moreover, the nanoparticles can release the encapsulated curcumin in response to a reducing environment, a characteristic of cancer cells compared to health cells. Consequently, the synthesized protein–polymer nanoparticles are more effective in inducing cancer cell death compared to the control nanoparticles, demonstrating their potential as an effective and targeted drug delivery system for cancer therapy.